Aplikasi Persediaan Menggunakan Metode Rata-Rata pada UD. Makanan Ringan Rumah Adat Minang - Gabriela Lumban Tobing; Rena Nainggolan; Eviyanti Novita Purba (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
Inventory of goods is goods available in a shop or trading company for sale and purchase to meet consumer demand. However, the inventory of goods must be checked periodically so that there is no stock shortage of the goods. This will make the form of service to consumers worse. So making decisions regarding stock of goods becomes difficult because information regarding the availability of goods is not provided quickly and accurately. The aim of this research is to answer the above problems that UD still faces. Minang Traditional Home Snacks. UD. Minang Traditional House Snacks is a trading business that sells various snacks. There is a need for a web-based application to be able to manage the supply of these snacks. The results and conclusions of this research are that this application can operate regarding purchases (incoming goods) and sales (outgoing goods) in providing this stock. This results in an inventory card containing information on purchase transactions, sales expenses and inventory in the form of a report that can be printed. With this application, it becomes easier for the owner to run his trading business, especially managing snack supplies, compared to not using the application.